The prophet - Gibran, Kahlil, 1883-1931 (Essential pocket classics, 2021)
"A new edition of the beloved spiritual classic Kahlil Gibran's The Prophet is a timeless classic, a guiding light of spiritual fiction that has shaped the hearts and souls of readers since it was first published in 1923. Translated into more than 40 languages around the globe, The Prophet is an inspirational work of art, a thought-provoking glimpse into the human heart, and transformational spiritual journey. The book begins when a prophet named Almustafa shares his wisdom over the course of eight essays. In these brief, poetic pieces he touches on the deepest profundities of life-pain and loss, friendship and love, joy and sorrow. This new, pocket-sized version of the classic work is true to the text of the first edition and features Gibran's original illustrations, bringing his writing to a new generation of readers"--